Reliability of B-mode ultrasound and shear wave elastography in evaluating sacral bone and soft tissue characteristics in young adults with clinical feasibility in elderly. Issue 2 (May 2022) - Abou Karam, Maher; Mukhina, Ekaterina; Daras, Nils; Rivals, Isabelle; Pillet, Hélène; Skalli, Wafa; Connesson, Nathanaël; Payan, Yohan; Rohan, Pierre-Yves
Abstract: Background: Physiologic aging is associated with loss of mobility, sarcopenia, skin atrophy and loss of elasticity. These factors contribute, in the elderly, to the occurrence of a pressure ulcer (PU). Brightness mode ultrasound (US) and shear wave elastography (SWE) have been proposed as a patient-specific, bedside, and predictive tool for PU. However, reliability and clinical feasibility in application to the sacral region have not been clearly established. Method: The current study aimed to propose a simple bedside protocol combining US and SWE. The protocol was first tested on a group of 19 healthy young subjects by two operators. The measurements were repeated three times. Eight parameters were evaluated at the medial sacral crest. Intraclass Correlation Coefficient (ICC) was used for reliability assessment and the modified Bland Altman plot analysis for agreement assessment. The protocol was then evaluated for clinical feasibility on a healthy older group of 11 subjects with a mean age of 65 ± 2.4 yrs. Findings: ICC showed poor to good reliability except for skin SWE and hypodermis thickness with an ICC (reported as: mean (95%CI)) of 0.78 (0.50–0.91) and 0.98 (0.95–0.99) respectively. No significant differences were observed between the young and older group except for the muscle Shear Wave Speed (SWS) (respectively 2.11 ± 0.27 m/s vs 1.70 ± 0.17 m/s). Interpretation: This is the first protocol combining US and SWE that can be proposed on a large scale in nursing homes. Reliability, however, was unsatisfactory for most parameters despite efforts to standardize the protocol and measurement definitions. Further studies are needed to improve reliability. Highlights: In the elderly sarcopenia, skin atrophy and loss of elasticity contribute to the occurrence of a pressure ulcer (PU). Bedside B-mode US and SWE protocol to evaluate skin, hypodermis, and muscle morphology and mechanical properties. The protocol was tested for reliability on 19 healthy young subjects, and clinical feasibility on 11 healthy older people. Reliability was mostly unsatisfactory despite efforts to standardize protocol and measurement definitions. Perspective work will review protocol to increase reliability and evaluate risk in elderly in nursing homes.